1998
DOI: 10.1021/la980823q
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, AFM, and NSOM Studies of 3D Crystallites in Mixed Langmuir−Blodgett Films of N,N‘-Bis(2,6-dimethylphenyl)-3,4,9,10-perylenetetracarboxylic Diimide and Stearic Acid

Abstract: Nonamphiphilic N, 4,9, has been incorporated in Langmuir-Blodgett (LB) films mixed with stearic acid (SA). Steady-state spectroscopic studies of the LB-deposited films on quartz substrates indicate an extensive broadening and shift of the absorption and emission spectra, suggesting molecular aggregation. Perhaps the most interesting spectral feature observed in this study is the observation of a broad emission band with its maximum at 650 nm. Concentration dependent studies demonstrate that, with increasing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…, 1999; Dunn, 1999). The combination of AFM and NSOM has been shown to be a powerful technique for studying phase‐separated phospholipid monolayers and bilayers (Dutta et al. , 1999; Hwang et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 1999; Dunn, 1999). The combination of AFM and NSOM has been shown to be a powerful technique for studying phase‐separated phospholipid monolayers and bilayers (Dutta et al. , 1999; Hwang et al.…”
Section: Introductionmentioning
confidence: 99%
“…The first band remains unchanged for the SA:Si‐PCPDTBT LB films; however, the second band undergoes a blue shift to 659 and 661 nm for 4:1 and 8:1, respectively. Since films of high ordering display a red‐shifted π−π* absorption band as well an increase in bandwidth, it can be concluded that at different levels the SA:PCPDTBT LB films have a more organized structure than those of SA:Si‐PCPDTBT.…”
Section: Resultsmentioning
confidence: 99%
“…However, the first experimental proof was presented by Pohl [2]. Both AFM and NSOM methods are crucial for many fields of science, technology, and industry, and are usually used separately [3][4][5]. These complementary methods are widely used for nanoscale study and characterization of new nanomaterial components, life science and biological objects [6], semiconductor and electronic metrology, and in photonics and plasmonics [7].…”
Section: Surface Scanning Background and Needsmentioning
confidence: 99%